Hematopoietic clonal dominance, stem cell mutations, and evolutionary pattern of JAK2V617F allele burden in polycythemia vera. (13th September 2014) - Angona, Anna; Alvarez‐Larrán, Alberto; Bellosillo, Beatriz; Martínez‐Avilés, Luz; Camacho, Laura; Fernández‐Rodríguez, Concepción; Pairet, Silvia; Longarón, Raquel; Ancochea, Águeda; Senín, Alicia; Florensa, Lourdes; Besses, Carles
Abstract Objectives Clonal dominance is characteristic of patients with post‐polycythemia vera myelofibrosis (post‐PV MF), whereas patients in chronic phase usually display polyclonal hematopoiesis. The aim of this work was to study the mutational burden of JAK2V617F at the progenitor level in patients with PV and correlate it with the evolutive phase of the disease and the presence of mutations in genes different to JAK2V617F. Methods JAK2V617F was measured in stem cells, progenitor cells, and granulocytes of 45 patients with PV (early chronic phase n = 26, late chronic phase n = 10, post‐PV MF n = 9). In addition, screening of TET2, DNMT3A, ASXL1, SF3B1, SRSF2, U2AF1, and TP53 was performed with quantification of the mutation in CD34+ cells in positive cases. Moreover, we assessed whether JAK2V617F allele burden in granulocytes (at a single time point or monitoring) could be used as a surrogate of clonal dominance. Results Ten patients presented clonal dominance at progenitor level (PV at diagnosis n = 2, late chronic phase n = 1, post‐PV MF n = 7). Additional mutations were identified in four patients at diagnosis, three in TET2, and one in DNMT3A gene, with clonal dominance present in three of them. At PV diagnosis, clonal dominance was demonstrated only in patients with additional mutations. JAK2V617F monitoring showed better diagnostic accuracy than single time point measurement as a marker of clonal dominance. Conclusions Clonal dominance may be present at diagnosis, especially in those cases carrying other mutations. JAK2V617F monitoring during follow‐up could help in the identification of patients with clonal dominance.